How do children perceive punishment in the family? - Maleš, Dubravka (Array, 2009)
Punishing children has always been a part of family upbringing, and various forms of punishment are applied today, too. However, while in the past parents had unlimited power over their children, today many countries, including the Republic of Croatia, have laws that regulate the parental right to physical and humiliating punishment of their children. Apart from physical punishment there are also other types of punishment that are used by parents in order to eliminate undesired children's behaviours, which may be very detrimental to their development. A theoretical and empirical study of these issues was conducted in an effort to find out how children perceive the process of punishment in the family. The theoretical part offers an overview of basic punishment related terms, while the empirical part investigates the forms of punishment in the family and how they are perceived by primary school pupils in grades 7 and 8, as well as differences that occur depending on the pupils' gender and grade. The obtained results suggest that a wide range of physical and non-physical punishment are applied in the subjects' families, with forms of punishment not involving corporal punishment being more common. Also, the study showed that a large number of subjects is not sufficiently informed of their rights and the law on physical punishment that is enforces in the Republic of Croatia. The results of the study maly help raise awareness in parents about the consequences of their disciplinary actions as well as foster educating chuldren on their rights.